SCRUB GULA DAN MADU UNTUK MERAWAT BIBIR KERING - Agus Susanti; Alvi Rizqia; Martina Dwi; Rafika Suryawati (Garina, 2021)
Dry lips are caused by the effect of the epidermis tissue of the lips both in cold and hot temperatures. The lip scrub moisturizes and nourishes the lips, making them look fuller, healthier, and hydrated. This study aims 1) to determine and explain the process of making Sugar and Honey Scrub. 2) To find out how to use Sugar and Honey Scrub on dry lips. 3) To know the changes of dry lips after doing Sugar and Honey Scrub. The method used in this research is experimental research, literature, documentation and interviews. The experiment was carried out at the Laboratory of the Cosmetology Study Program of the Kartini Academy of Social Welfare, Jalan Sultan Agung, No.77, Gajahmungkur Village, Gajahmungkur District, Semarang City. The formula is 1) 17g sugar, 10g honey 2) 17g sugar, 7g honey 3) 11g sugar, 6g honey. Experimental research results show Sugar and Honey Scrub in the third experiment, 11g honey and 6g sugar produce pale yellow color, sugar aroma, soft texture. The public test was carried out to 30 Panelists. In the third experiment, the average color was 1.7, Aroma 2.4 and Texture 2.7. Changes After 1 time using the Sugar and Honey Scrub, the lips look moist, supple and healthier. Thus, it can be concluded that there is a new innovation opportunity, namely Sugar and Honey Scrub for treating dry lips.